Penggunaan Disfemisme dalam Tuturan Anak Usia 4 Tahun: Kajian Semantik - Hastuti, Nur Fuji; Denafri, Bram (Jurnal Bahasa dan Sastra, 2024)
This study aims to elucidate the types and functions of dysphemism in the speech of four-year-old children. This research is warranted due to the prevalence of dysphemism observed in the social contexts of early childhood communication. The study employs a case study research design, with data obtained from the speech of four-year-old children that incorporates dysphemism. A qualitative methodology is adopted, utilizing a semantic perspective grounded in the theoretical framework established by Allan and Burridge regarding dysphemism. Data collection involved listening to and recording utterances that contained dysphemism. The observational method was employed for data gathering, with the fundamental technique being the tapping technique. Advanced techniques included listening, recording, and note-taking. The analysis of the data was conducted using the referential identity method, facilitating the determination of the reference of dysphemistic utterances. Furthermore, a distributional method was also applied in the analytical process. In this investigation, the types of dysphemism are analyzed in accordance with Allan and Burridge's theoretical framework. In addition, the types of dysphemisms are studied through Chaer's theory and the functions of dysphemisms proposed by Allan and Burridge. The most frequently employed type of dysphemism within the informants' speech is identified as cross-cultural dysphemism, while ist dysphemism is the least utilized. Among the functions of dysphemism, the predominant function observed in the informants' speech is the expression of anger, while the functions of cursing, allusion, and humiliating individuals are the least employed. The implications of this study underscore the significance of dysphemism in early childhood speech, indicating a need for support from the social environment to aid children in acquiring age-appropriate vocabulary.